Indian banking in international perspective - Reddy, Y. V. (Mumbai, India : The A.D. Shroff Memorial Trust, 2002)
The lecture was on Banking delivered by Dr. Y. V. Reddy, Executive Director, International Monetary Fund, and ex-Deputy Governor of Reserve Bank of India.
ne 11/08/2021
Loans
Keywords: International banking; Banking; India